Thermoacoustic Lensing in Ultrasound Imaging of Nonechogenic Tissue During High-intensity Focused Ultrasound Exposure. (May 2018) - Jahns, Matthew; MacDougall, Dan; Adamson, Robert B. A.
We develop a ray-tracing theory to describe the effects of thermoacoustic lensing during high-intensity focused ultrasound (HIFU) on ultrasound images of reflectors lying distal to the HIFU focal region and discuss the application of thermal lensing effects to dose monitoring in HIFU therapy. By analyzing the effects of thermal and geometric delays of acoustic rays passing through a region of tissue undergoing localized heating, we show how the shape of a reflector distal to the heated region can be predicted and present experimental measurements in good agreement with the model. We also apply the model in reverse to estimate the thermal profile of a heated region based on a measured change in the shape of a distal reflector during HIFU delivery. As an example, we apply this technique to the measurements of thermal diffusion in porcine fat. An interesting aspect of the technique is that it can be applied to measure temperature in nonechogenic tissues as long as there is an observable reflector in the ultrasound images that is located distal to the region of localized heating.